Can rats solve the active place avoidance task without the room-bound cues - Fajnerová, Iveta; Kenney, Jana; Lobellová, Veronika; Okrouhlicova, Sarka; Stuchlík, Aleš; Klement, Daniel (Behavioural brain research, 2014)
The active place avoidance task is used in the research of spatial cognition. Rats are trained on a rotating arena to avoid an aversive stimulus delivered in a part of the room while being transported toward it by the arena rotation. The task tests the ability of rats to navigate with respect to distal cues in the room and to ignore confusing cues on the arena. The demand for cue segregation makes the task suitable for studying neural mechanisms responsible for cognitive coordination. An incidental observation made in our laboratory implied that overtrained rats may be able to solve the task without the room-bound cues. The aim of this study was to test this observation. The room-bound cues were hidden by switching off the lights. Rats trained only in darkness did not learn the task at all. Rats that were initially pre-trained in light performed considerably better. In a few exceptional dark sessions they even reached the level of performance observed in light. The rats needed the aversive stimuli to keep off the to-be-avoided sector. Without them, they continued their behavior, but with no spatial relationship to the to-be-avoided sector. We conclude that rats are able to solve the place avoidance task without the room-bound cues, but not as efficiently as in their presence.
Keywords: potkani Long-Evans; plnění a analýza úkolů; Spatial Learning; prostorové učení; zvířata; učení vyhýbat se; Task Performance and Analysis; zraková percepce; mužské pohlaví; Visual Perception; psychologické testy; Psychological Tests; tma; Animals; elektrický šok; podněty; Rats, Long-Evans; Avoidance Learning; Cues; Darkness; Male; Electroshock